Ungrading in organic chemistry: students assessing themselves and reflecting on their learning - Ferguson, Jalisa H.; Bonner, Lisa A. (Frontiers in Education, 2024)
The focus on grades has diminished the focus on learning. One strategy that aims to return students' attention to what they are actually learning (and not just earning) is ungrading. Ungrading is thought of as any strategy in which instructors do not assign a number or letter grade to students' assignments and assessments. Instead, faculty may 1) provide thorough feedback and engage in dialogue with students about their work, and perhaps, 2) allow students to assign their own grade. Whichever style of ungrading they choose, the scholars that have been forging the path for ungrading come from a variety of fields and perspectives, including STEM instructors in more recent years. The focus on incorporating ungrading practices into the organic chemistry curriculum provided here is adapted from a variety of practitioners, and especially the foundational work of chemistry professor Clarissa Sorensen-Unruh. In addition to discussing the current ungrading practices in various fields, we will use this perspective article to share our own experience with and lessons learned from beginning to incorporate ungrading in the undergraduate organic chemistry curriculum, both as it relates to the implementation of the practice and our own perceptions of the student experience and learning outcomes. Ultimately, the goal is to allow students to see the significance of the process of learning and to engage in some metacognitive work that they can apply to different assignments, whether in our class or not. If we want students to focus on learning, perhaps they should do the grading themselves.